The Effect of Noise and Lighting on Physiological and Psychological Health of Manufacturing Industry Workers - Wijayantono, Wijayantono; Lindawati, Lindawati; Afridon, Afridon (Asian Journal of Healthcare Analytics, 2025)
This study examines how noise levels and lighting intensity affect the physiological and psychological health of manufacturing workers. Using a quantitative explanatory design with a cross-sectional survey, data were collected from 80 workers through noise and lighting measurements as well as questionnaires assessing blood pressure, fatigue, and stress. Multiple regression analysis shows that both noise and lighting significantly influence workers' health, with noise having a stronger impact on stress and fatigue. The findings highlight the need for effective workplace environmental controls to protect workers’ well-being and support productivity.